ANALISIS PENGARUH KEPEMIMPINAN, MOTIVASI KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Gombel Golf Semarang) - Prameswari, Ajeng Anggi; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2016)
This study is motivated by the performance level ofemployees at gombel golf semarang which has not optimal. Based on the results of pre â€“ survey,Â decrease employee performance problem that occurs is indicated by the leadership, motivation, and work discipline in supporting the process of employee performance.This studyaims to examineandanalyze the effect ofleadership, motivation work, and discipline work on the performance ofemployees of Gombel GolfSemarang.This study uses three independent variables are leadership, motivation, and discipline of working with one dependent variable is the performance of employees. Using the formula slovin, obtained a sample of 52 employees. And the data collection methods used in this study is a questionnaire distributed to a sample that has been determined.The data analysis methodusedin this study includevalidity,reliability, classic assumption test, multiple linear regression analysis, t test, andthe coefficient of determination. Based on the results of t - test and multiple linear analysis showed that all hypothesis is accepted. Which meanÂ leadership, work motivation, and work discipline have apositive effect and significant on employee performance.